Major powers' nuclear policies and international order in the 21st c entury : 2009 NIDS International Symposium on Security Affairs. - NIDS International Symposium on Security Affairs 2009 : Tokyo, Japan); Boeicho Boei Kenkyujo (Japan) ([Tokyo] : National Institute for Defense Studies, 2010)
This is a report of the proceedings of the 12th International Sympos ium on Security Affairs hosted by the National Institute for Defense St udies (NIDS) on 18 November 2009. At the symposium, entitled "Major Pow ers' Nuclear Policies and International Order in the 21st Century," dis tinguished experts from China, France, India, Japan, Russia, the UK and the US explored the role of nuclear weapons and the future of internat ional order from various viewpoints. These issues represent some of the greatest challenges the international community faces in the 21st cent ury.
The role of nuclear weapons in the 21st century / Morton H. Halperin -- Agenda for Japan-US strategic consultations / Yukio Satoh -- The Ob ama administration's nuclear policy and implications for East Asian sec urity / M. Elaine Bunn -- Russia's nuclear policy / Yury E. Federov -- China's nuclear policy and international order in the 21st century / Li ping Xia -- India's nuclear policy / Rajesh Rajagopalan -- The "forward leaning" nuclear state : the UK and nuclear weapons in an era of strat egic uncertainties / John Simpson -- Nuclear deterrence and disarmament : the view from Paris / Bruno Tertrais.
"Date of publication: July 2010"--T.p. verso.
Includes bibliographical references.
Also available online in PDF format from National Institute for Secu rity Studies (Japan) web site. Adobe Acrobat Reader required.
Keywords: Nuclear disarmament -- Congresses; Nuclear weapons -- Government policy -- Japan -- Congresses; Nuclear weapons -- Government policy -- United States -- Congresses; Nuclear weapons -- Government policy -- Russia (Federation) -- Congr esses; Nuclear weapons -- Government policy -- China -- Congresses; Nuclear weapons -- Government policy -- India -- Congresses; Nuclear weapons -- Government policy -- Great Britain -- Congresses; National security -- East Asia -- Congresses; Security, International